PERANCANGAN ELEKTRO EJAKULATOR SEBAGAI ALAT BANTU INSEMINASI BUATAN PADA KAMBING TERNAK DI KOTA BENGKULU - Irnanda Priyadi; Faisal Hadi; Doni Tamara; Makmun Reza Razali (Teknosia, 2022)
Semen collection is one of the activities contained in the artificial insemination program in animals. Semen collection can be done in several ways, namely using an artificial vagina, massage and using an electro ejaculator module. The use of the electro ejaculator module is a safe and appropriate method for male livestock. Electro ejaculator module sold in the market has a relatively expensive price and is still difficult to find, especially in Indonesia. Therefore, an electro ejaculator module or device for goats is needed that has an affordable price so that it can be used by small to medium-sized farms. This electro ejaculator device consists of 3 main parts, namely Switch Mode Power Supply, function generator and an electro ejaculatory probe. At the testing stage of the switch mode power supply (SMPS) section, the output voltage variation is obtained from 0 - 15 volts. While in the function generator section, the output signal is in the form of a sinusoidal which can be adjusted for the amplitude and the output frequency from 0 - 1 Mhz. Based on these results, the designed Electro Ejaculator module can be applied to assist the process of artificial insemination in animals.